The influence of Niels Bohr on Max Delbrück: revisiting the hopes inspired by "light and life" - McKaughan, Daniel J (Isis, 2005)
The impact of Niels Bohr's 1932 "Light and Life" lecture on Max Delbrück's lifelong search for a form of "complementarity" in biology is well documented and much discussed, but the precise nature of that influence remains subject to misunderstanding. The standard reading, which sees Delbrück's transition from physics into biology as inspired by the hope that investigation of biological phenomena might lead to a breakthrough discovery of new laws of physics, is colored much more by Erwin Schrödinger's What Is Life? (1944) than is often acknowledged. Bohr's view was that teleological and mechanistic descriptions are mutually exclusive yet jointly necessary for an exhaustive understanding of life. Although Delbrück's approach was empirical and less self-consciously philosophical, he shared Bohr's hope that scientific investigation would vindicate the view that at least some aspects of life are not reducible to physico-chemical terms.